Self-healing Materials: Unlocking New Potential in Membrane Technology (Journal of Applied Membrane Science & Technology, 2024)
Damage to the membrane is a significant challenge in membrane filtration process. Water pollution has emerged as a significant environmental issue due to the rising of untreated or partially treated wastewater being directly discharged into the rivers or oceans. Self-healing material that has the ability to localise response to damage in the meantime has come under the spotlight as the alternative means to cope with the issue of declined performance of membrane due to mechanical abrasion. It can be classified into two categories which are extrinsic and intrinsic, respectively. Extrinsic self-healing relies on the integrated healing agent in the membrane matrix that response to damage while intrinsic self-healing depends on the dynamic bonds between the polymeric materials that will trigger the autonomous repair through reversible chemical bonds. This short review provides an overview of the self-healing mechanisms of various materials and their potential for developing membrane with self-healing capability.
Keywords: Water pollution, self-healing, membrane, extrinsic, intrinsic